linear eqns in 2 variable..

Asked by  | 15th Feb, 2010, 11:10: PM

Expert Answer:

Use cross multiplication, do it step by step so don't make any mistake.

(a-b)x + (a+b)y = a2 - 2ab - b2

(a+b)x + (a+b)y = a2 + b2

Subtracting the two equations,

(a-b)x - (a+b)x =   (a2 - 2ab - b2)-(a2 + b2)

-2bx = -2ab-2b2

x = a+b

Use this in the given equations,

(a+b)x + (a+b)y = a2 + b2   

(a+b)(a+b) + (a+b)y = a2 + b2   

a2 + 2ab + b2 + (a+b)y = a2 + b2  

y = -2ab/(a+b)

Regards,

Team,

TopperLearning.

Answered by  | 16th Feb, 2010, 05:18: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.